A prática de uma professora de Matemática ao conduzir uma discussão coletiva sobre sequências - Rodrigues, Cátia (2018)
Mathematics learning with understanding can be improved by engaging students in whole-class discussions as they are called upon to present, justify and argue their strategies and the strategies of their colleagues and, later, to systematize the main ideas emerging from this discussion. This qualitative and interpretive study, is a case study of a grade 7 mathematics teacher, and aims to understand this practice in conducting the whole-class discussions, in connection with her didactic knowledge, when exploring a task involving sequences. The results show that the teacher, based on her didactic knowledge and preparation of the lesson, organizes the whole-class discussion in three moments (presentation; comparison, evaluation and filtering; and conclusion) in which she undertakes various teaching actions.